Seropositivity for Listeria monocytogenes in Women with Spontaneous Abortion: A Case-Control Study in Iran - Mahin Jamshidi; Abdolreza Sotoodeh Jahromi; Parivash Davoodian; Malihe Amirian; Mehrangiz Zangeneh; Fatemeh Jadcareh (Elsevier, 2009)
Objective: There are many studies supporting the role of certain asymptomatic infections such as Listeria monocytogenes (L. monocytogenes) in spontaneous abortion. In some cases, latent listeriosis may complicate the pregnancy, and serologic tests can, therefore, be used to detect the disease. This study was designed to assess the relationship between seropositivity for L. monocytogenes and spontaneous abortion. Materials and Methods: A total of 250 women with previous spontaneous abortion and a control group of 200 women with normal full-term deliveries entered the study as case and control groups, respectively. Demographic characteristics were recorded for each subject, and serum samples were obtained from all participants. All serum samples were examined using the indirect immunofluorescence antibody test for L. monocytogenes antibody. Data was analyzed using Chi-squared and t tests. Results: The average age of participants was 25.6 ± 7.6 years in cases and 25.3 ± 6.5 years in controls. Eighty-nine (35.6%) of the cases with abortion and 35 (17.5%) of the control group were positive for L. monocytogenes antibody (p = 0.001). No relationship was observed between the number of pregnancies and infection with L. monocytogenes (p = 0.4), or between the number of previous abortions and L. monocytogenes seropositivity (p = 0.2). Conclusion: We suggest monitoring L. monocytogenes seroprevalence in pregnant women at high risk of threatened abortion, and further microbiological assessment of symptomatic women for detection of L. monocytogenes and insidious infection.